2020
DOI: 10.3847/1538-3881/ab4e93
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Bayesian Framework for Assessing Habitability with Joint Observational and Model Constraints

Abstract: The catalog of stellar evolution tracks discussed in our previous work is meant to help characterize exoplanet host-stars of interest for follow-up observations with future missions like JWST. However, the utility of the catalog has been predicated on the assumption that we would precisely know the age of the particular host-star in question; in reality, it is unlikely that we will be able to accurately estimate the age of a given system. Stellar age is relatively straightforward to calculate for stellar clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 80 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…For instance, the biosignature search community is developing many mature frameworks for designing and interpreting the results of life detection experiments, including the development and selection of good biosignatures to search for, selection criteria and prioritization of target lists, and frameworks for determining the confidence of detection and dealing with ambiguity (Stark et al 2019;Truitt et al 2020;Tuchow & Wright 2020, 2021Neveu et al 2018;Green et al 2021, to give a few recent examples in addition to the references in Section 1).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the biosignature search community is developing many mature frameworks for designing and interpreting the results of life detection experiments, including the development and selection of good biosignatures to search for, selection criteria and prioritization of target lists, and frameworks for determining the confidence of detection and dealing with ambiguity (Stark et al 2019;Truitt et al 2020;Tuchow & Wright 2020, 2021Neveu et al 2018;Green et al 2021, to give a few recent examples in addition to the references in Section 1).…”
Section: Discussionmentioning
confidence: 99%
“…Values for the fixed age required for sustained habitability range in the literature from 2 Gyr to 4 Gyr (Truitt et al 2020). If one were to select 2 Gyr as the habitable duration required to host biosignatures, then H would have the functional form:…”
Section: Relative Biosignature Yield Metricsmentioning
confidence: 99%
“…The coefficients encapsulate underlying assumptions of the atmospheric modeling and the weather on the planet, as well as of the properties of the surface of the planet and other unknown planet properties that are beyond the scope of this, and indeed most, papers. We found that there is a lack of general consensus in the literature as to what these parameters should be, and an overall disagreement in the models that should be applied (e.g., Kokaia et al 2020;Truitt et al 2020 Abe et al 2011). In choosing our model parameters for the Really Habitable Zone, we therefore followed what appears to be standard practice, and made-up new coefficients entirely as shown in Table 1 according to our whims.…”
Section: Determining the Really Habitable Zonementioning
confidence: 99%